MANAJEMEN SISTEM PENGELOLAAN LOGISTIK BARANG NON MEDIS DI RUMAH SAKIT ANDIMAS KABUPATEN MERANGIN: MANAJEMEN SISTEM PENGELOLAAN LOGISTIK BARANG NON MEDIS DI RUMAH SAKIT ANDIMAS KABUPATEN MERANGIN - Yeyen Gustina Irawan (ARUMAS, 2024)
Background : The hospital is a business unit of production in the form of conducting health services, which is one of the logistical aspects of the important aspects of a successful production of these services. Likewise, the non-medical logistics inventory items in it, is needed in order to support health services in the hospital. Berdasarkan initial survey on the management of non-medical logistics Andimas Hospital in Merangin, looks to have tersistem well as the presence of skilled human resources and responsible and supported by adequate facilities. Methods : This study is a descriptive qualitative research, which is located at Andimas Hospital in Merangin. Data was collected through interviews and check list, the study subjects head of household and non-medical logistics section chief. Evaluation is done in stages, ie evaluation of the inputs, processes and outputs of non medical logistics management. The evaluation of the inputs made to the elements of the system that includes human resources and facilities . The evaluation of the process is done by looking at the activities that run non-medical goods logistics management, while the evaluation of the output is done by looking at the availability of non-medical goods logistics in Andimas Hospital in Merangin perform health services. Results : The results showed that the human resources in accordance with the requirements for its member been structured and able to function properly. Meanwhile, the management of logistic facilities in non-medical look is in conformity with the standards for size storage shed although not according to the standard. Evaluation of the process shows that the non-medical goods logistics management is pretty good because it has remained in its execution procedures. While the evaluation of the output shows that the output has been meeting the needs of health and support services at the hospital. Conclusion : Logistics management system non-medical goods Andimas hospital Merangin district according to the standard because it has been able to support the public health  services in accordance with the Act on Health of the Republic of Indonesia, 23 1992. Advice to the hospital in order to expand the storage shed to match the standards set . Keywords : Logistics Management Systems Non-Medical Items In Hospital.